2018
DOI: 10.1002/cctc.201801022
|View full text |Cite|
|
Sign up to set email alerts
|

Surprising Differences of Alkane C‐H Activation Catalyzed by Ruthenium Nanoparticles: Complex Surface‐Substrate Recognition?

Abstract: The activation of CÀH bonds of alkanes remains a major challenge for chemistry. In a series of deuteration experiments with D 2 in contact with bis-(diphenylphosphino) butane (dppb) stabilized ruthenium nanoparticles (liquid substrates, 60 8C, 6 bar D 2 ) we have observed a surprisingly large reactivity of cyclopentane as compared to cyclohexane and other alkanes. DFT calculations using a ligand-free Ru 13 H 17 model cluster as catalyst indicate oxidative CÀH cleavage of the bound substrates as rate limiting r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Similar results are also observed for the fraction of butane (Figure ). This observation is in excellent agreement with the deuteration of alkanes on Ru/dppb MNPs as demonstrated in our previous work …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Similar results are also observed for the fraction of butane (Figure ). This observation is in excellent agreement with the deuteration of alkanes on Ru/dppb MNPs as demonstrated in our previous work …”
Section: Resultssupporting
confidence: 93%
“…Together with the results from our former paper on alkane deuteration a variety of side reactions can be identified as illustrated in Figure . The reaction steps A1 and A2 describe the C−P bond cleavage catalyzed by the particle that leads to the formation of benzene and butane.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…24,25 The combination of these reactivities may render the NPs active catalysts for H/D exchange, which in turn can serve as a good model reaction to understand the surface reactivity and selectivity of the MNPs. 26 For instance, our research groups have already shown that Ru NPs can efficiently catalyze C-H activation reactions leading to selective deuterium incorporation into several nitrogen-containing compounds such as pyridines, indoles, alkylamines, etc. 27,28 Later on, it was shown that Ru and RuPt NPs are good catalysts for the enantiospecific deuteration of peptides at the α position of nitrogen atoms.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Later on, it was shown that Ru and RuPt NPs are good catalysts for the enantiospecific deuteration of peptides at the α position of nitrogen atoms. [24][25][26][27][28][29] However, a typical limitation of Ru-based NPs in H/D exchange reactions is their high reactivity towards aromatic rings, leading, in some cases, to the formation of considerable amounts of undesired reduced side-products. 30,31 In this respect, Ni NPs, less prone to hydrogenate aromatic rings, can appear as a more earth-abundant and less-costly alternative to Ru NPs for H/D exchange reactions.…”
Section: Introductionmentioning
confidence: 99%